2012
DOI: 10.1042/bsr20120046
|View full text |Cite
|
Sign up to set email alerts
|

Protein instability and functional defects caused by mutations of dihydro-orotate dehydrogenase in Miller syndrome patients

Abstract: Miller syndrome is a recessive inherited disorder characterized by postaxial acrofacial dysostosis. It is caused by dysfunction of the DHODH (dihydroorotate dehydrogenase) gene, which encodes a key enzyme in the pyrimidine de novo biosynthesis pathway and is localized at mitochondria intermembrane space. We investigated the consequence of three missense mutations, G202A, R346W and R135C of DHODH, which were previously identified in patients with Miller syndrome. First, we established HeLa cell lines stably exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 22 publications
2
13
0
2
Order By: Relevance
“…Mandibulofacial dysostosis (OMIM610536) with microcephaly syndrome shares some overlapping features with Treacher Collins syndrome and has been associated with disruption of a spliceosomal GTPase [Lines et al, 2012; Luquetti et al, 2013]. Among several acrofacial dysostoses, causative mutations have recently been identified in an enzyme involved in pyrimidine biosynthesis in association with Miller syndrome (OMIM 263750) [Fang et al, 2012;], and in a component of the pre-mRNA spliceosomal complex, with respect to Nager syndrome (OMIM 154400) [Bernier et al, 2012]. Here we explore recent progress in understanding the etiology, pathogenesis and management of Treacher Collins, Nager and Miller syndromes and the potential for therapeutic prevention of facial dysostoses (Fig.…”
Section: Facial Dysostosismentioning
confidence: 99%
“…Mandibulofacial dysostosis (OMIM610536) with microcephaly syndrome shares some overlapping features with Treacher Collins syndrome and has been associated with disruption of a spliceosomal GTPase [Lines et al, 2012; Luquetti et al, 2013]. Among several acrofacial dysostoses, causative mutations have recently been identified in an enzyme involved in pyrimidine biosynthesis in association with Miller syndrome (OMIM 263750) [Fang et al, 2012;], and in a component of the pre-mRNA spliceosomal complex, with respect to Nager syndrome (OMIM 154400) [Bernier et al, 2012]. Here we explore recent progress in understanding the etiology, pathogenesis and management of Treacher Collins, Nager and Miller syndromes and the potential for therapeutic prevention of facial dysostoses (Fig.…”
Section: Facial Dysostosismentioning
confidence: 99%
“…In total, 13 mutations from exon 2 to exon 9 in the DHODH gene have been reported in Miller syndrome [16,17]. Previously, we identified that the G202A and R346W mutations cause deficient protein stability, and the R135C mutation does not affect stability, but impairs the substrate-induced enzymatic activity, suggesting that impairment of DHODH activity is linked to the Miller syndrome phenotype [18]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on mammalian DHODH have shown that DHODH is physically associated with the respiratory chain complexes III and II (42). Moreover, depletion of DHODH induced cell cycle arrest and mitochondrial dysfunction (42)(43)(44). Here, we show that wild-type and mutant TgDHODH enzymes localized to the parasite mitochondria and that T. gondii expressing catalytically deficient DHODH retained an intact mitochondrial membrane potential even with reduced expression levels of catalytically deficient TgDHODH enzymes.…”
Section: Discussionmentioning
confidence: 69%